2014
DOI: 10.1002/aur.1408
|View full text |Cite
|
Sign up to set email alerts
|

Motor Deficits in Children With Autism Spectrum Disorder: A Cross‐Syndrome Study

Abstract: Recent research suggests that children with autism spectrum disorder (ASD) experience some level of motor difficulty, and that this may be associated with social communication skills. However, other studies show that children with language impairments, but without the social communication problems, are at risk of motor difficulties as well. The aim of the present study was to determine if children with ASD have syndrome‐specific motor deficits in comparison to children with specific language impairment (SLI). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
56
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 50 publications
(43 reference statements)
4
56
0
5
Order By: Relevance
“…In line with this, Ament et al [126] suggest that impairments in motor skills requiring the coupling of visual and temporal feedback to guide and adjust movement can differentiate ADHD, autism and developmental delay. McPhillips et al [134] have begun to extend this line of research to other developmental conditions by comparing children with autism and SLI. However, much further work is required before a 'movement signature' differentiating autism from other conditions can be identified.…”
Section: (I) Further Questionsmentioning
confidence: 99%
“…In line with this, Ament et al [126] suggest that impairments in motor skills requiring the coupling of visual and temporal feedback to guide and adjust movement can differentiate ADHD, autism and developmental delay. McPhillips et al [134] have begun to extend this line of research to other developmental conditions by comparing children with autism and SLI. However, much further work is required before a 'movement signature' differentiating autism from other conditions can be identified.…”
Section: (I) Further Questionsmentioning
confidence: 99%
“…Only one study investigated SLI: McPhillips et al (2014) found no significant difference in total motor skills, with the only difference being in one of the manual dexterity tasks where autistic children were significantly poorer at threading laces. This study apparently failed to control for multiple comparisons, but as this could result in false positives, the lack of difference in total motor score and subtests seems to reflect a genuine lack of difference in this group.…”
mentioning
confidence: 98%
“…Failing to match groups of HFA and AS individuals on IQ casts further doubt on supposed differences between them (Ghaziuddin & Butler, 1998), and on the findings of studies which do not control for IQ between groups or consider it in their analysis (problematically, this is not always reported). Language problems are of course often related to IQ and so naturally, autistic individuals with better current and/or historic language skills tend to perform superiorly in most motor tasks (Barbeau et al, 2015;Belmonte et al, 2013;Gernsbacher et al, 2008;Hsu et al, 2004;McPhillips et al, 2014): as we shall go on to discuss, language requires motor proficiency and so this is hardly surprising. Finally, a single study previously mentioned investigated motor differences between autistic children with and without developmental regression, finding different patterns of motor impairment which may reflect different pathological processes (Ozonoff et al, 2008).…”
mentioning
confidence: 99%
See 2 more Smart Citations